2020
DOI: 10.1021/acs.orglett.0c00160
|View full text |Cite
|
Sign up to set email alerts
|

Cyanomethylation of Substituted Fluorenes and Oxindoles with Alkyl Nitriles

Abstract: The first example of metal-free cyanomethylenation from alkyl nitriles of sp3 C–H bonds to afford quaternary carbon centers is described. This oxidative protocol is operationally simple and features good functional group compatibility. This method provides a novel approach to highly functionalized fluorene and oxindole derivatives, which are commonly used in material and pharmaceutical areas. Control experiments provide evidence of a radical reaction process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Although 1 has been widely used in acid-base catalysis, 30) its use in radical reactions is relatively rare. [12][13][14] We initiated this study with use of racemic Pd complex I as a catalyst for the proposed aerobic dimerization of 1 because the C(sp 3 )-C(sp 3 ) bond in 2 is readily cleavable even at room temperature, providing thermodynamically stable meso-2, rather than dl-2, as the major product. 8) We found that the use of CH 3 CN as the solvent is critical to obtain a high yield of meso-2a (Table 1, entry 1 vs. entry 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 1 has been widely used in acid-base catalysis, 30) its use in radical reactions is relatively rare. [12][13][14] We initiated this study with use of racemic Pd complex I as a catalyst for the proposed aerobic dimerization of 1 because the C(sp 3 )-C(sp 3 ) bond in 2 is readily cleavable even at room temperature, providing thermodynamically stable meso-2, rather than dl-2, as the major product. 8) We found that the use of CH 3 CN as the solvent is critical to obtain a high yield of meso-2a (Table 1, entry 1 vs. entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…8,9) The persistent radical 1 • is readily generated from 2, which contains an elongated C(sp 3 )-C(sp 3 ) bond, simply by heating without the assistance of redox-active transition metals. [8][9][10][11][12][13][14][15][16] However, the requisite dimers 2 were synthesized from the corresponding monomers 1 using a stoichiometric amount of K 3 [Fe(CN) 6 ] as an oxidant under basic conditions at 80°C according to the literature procedure. [16][17][18][19] In this Note, we describe a mild protocol for aerobic oxidative dimerization of 1 to provide the dimers 2 by using Pd-µ-hydroxo complex I, previously employed as an acid-base catalyst 20,21) (Chart 1, i).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In addition, cyanomethyl moieties obtained via cyanomethylation are found as versatile motifs in some important bioactive natural products and drugs. 4,5 A variety of protocols have been reported, including transition-metalcatalyzed methods [6][7][8][9][10][11][12][13][14][15][16] and metal-free catalyzed methods [17][18][19][20][21][22] for the synthesis of cyanomethyl-containing compounds. Compared to the toxic metal used, metal-free catalyzed methods used acetonitrile [9][10][11][12]17,18 and its analogs such as bromoacetonitrile, [13][14][15][16] cyanoacetic acid 19,20 and ethyl cyanoacetate 5 have drawn considerable attention due to its inexpensive and environmental-friendly properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metal-free cyanomethylation using of acetonitrile as a cyanomethyl source in the synthesis of the cyano-containing compounds was reported. 17,18,21 In 2016, Sun and co-workers 18 demonstrated a convenient and efficient method for the synthesis of 3-cyanomethylated coumarins, a class of very important heterocyclic compounds in pharmaceuticals and dyes, via cyanomethylation and cyclization of aryl alkynoates using acetonitrile as the cyanomethyl source in the presence of tert-butyl peroxybenzoate (TBPB) under metal-free conditions. A control experiment carried out in the presence of 2,6-di-tert-butyl-4-methylphenol (BHT) or 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) showed that the thermal cyanomethylation and cyclization of aryl alkynoates proceeds via a radicalic process as described in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reactions that incorporate these groups are highly desirable. Previously our group discovered the oxidative coupling of toluene and alkylnitriles with aryl malononitriles, oxindoles, and related substrates . These reactions are believed to proceed by the formation of a dimer intermediate that is in equilibrium with the reactive species, the captodative radical monomer, in solution at higher temperatures .…”
mentioning
confidence: 99%